1992
DOI: 10.1002/ijc.2910510119
|View full text |Cite
|
Sign up to set email alerts
|

An organoid culture assay (OCA) for determining the drug sensitivity of human tumors

Abstract: A model for testing chemotherapeutic agents in vitro is described. It is based on an organoid culture method which allows human carcinomas to grow in vitro and to maintain many typical in vivo properties, including 3-dimensional architecture, growth of multiple cell types, expression of morphological differentiation and formation of histotypical structures. The preservation of drug sensitivity and resistance under the conditions of our organoid culture assay (OCA) was demonstrated by investigating 3 strains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Until now, only one group described an “organoid culture assay” of HNSCC [ 86 , 87 ]. Although the authors did not use fresh primary tumor, they aimed for 3D in vitro tumor growth allowing to form organized and differentiated structures such as those existing in the organism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, only one group described an “organoid culture assay” of HNSCC [ 86 , 87 ]. Although the authors did not use fresh primary tumor, they aimed for 3D in vitro tumor growth allowing to form organized and differentiated structures such as those existing in the organism.…”
Section: Resultsmentioning
confidence: 99%
“…After 2 weeks of spheroid formation, a prediction assay warrants another 2 weeks of incubation. Within the first weeks a decreasing proportion of epithelial cells was seen [ 80 ] and a degeneration of histological characteristics [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that these organoid cultures maintained the critical properties of the in vivo state, such as the 3D architecture, the growth of heterogeneous cell types from an individual carcinoma and the morphological differentiation under relatively simple experimental conditions [7]. In a subsequent study, the same group demonstrated that these organoid cultures can be used for drug testing, and that the response data obtained thereof were concordant with patients' response to therapy [21]. The authors were the first to propose organoid cultures as personalized in vitro drug testing platform, allowing the prediction of individual chemosensitivity of carcinomas within few days [21].…”
Section: Advanced Ex Vivo Models Of Hnsccmentioning
confidence: 93%
“…In a subsequent study, the same group demonstrated that these organoid cultures can be used for drug testing, and that the response data obtained thereof were concordant with patients' response to therapy [21]. The authors were the first to propose organoid cultures as personalized in vitro drug testing platform, allowing the prediction of individual chemosensitivity of carcinomas within few days [21].…”
Section: Advanced Ex Vivo Models Of Hnsccmentioning
confidence: 99%
“…In light of this, National Cancer Institute (NCI) announced abolishment of using NCI-60 cancer cell lines for future drug screening tests [12]. 3D organoid culture was first developed in 1950s [13,14], but did not gain attention in drug screening until recent years [15,16]. The mimicry of 3D environment in organoid cultures is its major virtue, and proves it to be more closely representative of its primary tumor.…”
Section: Chemotherapy: a Double-edged Swordmentioning
confidence: 99%